2015
DOI: 10.1002/ejoc.201403519
|View full text |Cite
|
Sign up to set email alerts
|

Calixarene‐Mediated Liquid Membrane Transport of Choline Conjugates 2: Transport of Drug‐Choline Conjugates and Neurotransmitters

Abstract: Lower rim carboxylic acid calix[n]arenes and upper rim phosphonic acid functionalized calix[4]arenes effect selective transport of distinct molecular payloads through a liquid membrane. The secret to this success lies in the attachment of a receptor-complementary handle. We find that the trimethylammonium ethylene group present in choline is a general handle for the transport of drug and drug-like species. Furthermore, neurotransmitters possessing ionizable amine termini are also transported. Some limitations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…17,[21][22][23] Drug delivery and solubilization using calix[n]arenes or calix [4]resorcinarenes have been reported. [24][25][26][27][28][29][30][31][31][32][33][34][35][36][37][38] However, the use of calixarenes and calixresorcinarenes as drug delivery is still a relatively novel concept, and the number of experimental or computational studies reported so far is relatively low, despite that these macrocyclic compounds possess several advantages such as ease of synthesis and modification and low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…17,[21][22][23] Drug delivery and solubilization using calix[n]arenes or calix [4]resorcinarenes have been reported. [24][25][26][27][28][29][30][31][31][32][33][34][35][36][37][38] However, the use of calixarenes and calixresorcinarenes as drug delivery is still a relatively novel concept, and the number of experimental or computational studies reported so far is relatively low, despite that these macrocyclic compounds possess several advantages such as ease of synthesis and modification and low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…2 and Table 1). 31 Transport was enhanced 4.6 times when HEPES buffered source and receiving phases were used. The enhanced transport in HEPES was a surprise to us.…”
Section: Discussionmentioning
confidence: 99%
“…15 Our second study examined the nature of the payload and we found many drug and drug like entities were efficiently transported through a liquid membrane – usually at rates far superior compared to controls lacking a calixarene transporter. 31 Some limits obviously emerged, but also exciting results showing that serotonin and dopamine with a smaller ammonium handle were also transported. Concurrently, we serendipitously uncovered a third useful handle in the form of an ammonium dicarboxylate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by adjustable cavity, convertible conformation, easy chemical modification and functionalization, easy synthesis, inexpensive raw materials and so on [2] . In recent years, with in-depth study of host-guest chemistry, the functional modification and application of the calixarenes become a popular research topic in this field [3] .…”
Section: Introductionmentioning
confidence: 99%